Stylistic analysis of prose of Qajar period newspapers - Hasan Zolfaghari; Effat Hasani Kochaki (مطالعات زبانی و بلاغی)
Although the role of the press can be examined from a social, political and cultural perspective, it cannot be ignored that the emergence and expansion of the press has had a profound effect on our language; In particular, the influence of Persian prose on the press is undeniable. The press has a prominent place in the contemporary history of our country; Thus, the study of developments related to the contemporary history of our country without considering the role of the press will be incomplete. Stylistic analysis of the prose of twenty newspapers from the early years of journalism to the end of the Qajar period is the main subject of this research. In this research, an attempt has been made to examine the stylistic features of these newspapers in five related phonetic, lexical, syntactic, rhetorical and ideological layers. For this review, we selected 50% of the text of an issue from each newspaper. In this study, the citation research method was used and to answer the questions and information required, we also referred to the content of sources and references related to the research topic in the form of books, articles and dissertations. The results show that in the phonetic layer; Some historical variables are evident. Also, the music and the song resulting from the rhyme and the phonology (repetition of a phoneme) have somewhat added to the beauty of the text. In the lexical layer; Political codes, Shari'a, and Arabic and foreign interpretations have a high frequency. One of the characteristics of the syntactic layer is that it shortens most sentences as well as uses a basic style. In addition, a high percentage of the way to remove verbs is related to symmetry. In the ideological layer, the influence of layered stylistics, lexical and syntactic layer is well evident. Also, the stylistic features of the newspapers of this period were compared with the prose of the literary genre of the same period.